Implementation of ISO 9001:2000 quality management system for construction biddings procedures in construction management practice [compact disc] - 235515 Berreksi Youceff (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2006